Modification of Hypoxic Respiratory Response by Protein Tyrosine Kinase in Brainstem Ventral Respiratory Neuron Group. - Hui Wang; Ruituo Huai; Junqing Yang; Yanchun Li (PLoS ONE, 2016)
Protein tyrosine kinase (PTK) mediated the tyrosine phosphorylation modification of neuronal receptors and ion channels. Whether such modification resulted in changes of physiological functions was not sufficiently studied. In this study we examined whether the hypoxic respiratory response-which is the enhancement of breathing in hypoxic environment could be affected by the inhibition of PTK at brainstem ventral respiratory neuron column (VRC). Experiments were performed on urethane anesthetized adult rabbits. Phrenic nerve discharge was recorded as the central respiratory motor output. Hypoxic respiratory response was produced by ventilating the rabbit with 10% O2-balance 90% N2 for 5 minutes. The responses of phrenic nerve discharge to hypoxia were observed before and after microinjecting PTK inhibitor genistein, AMPA receptor antagonist CNQX, or inactive PTK inhibitor analogue daidzein at the region of ambiguus nucleus (NA) at levels 0-2 mm rostral to obex where the inspiratory subgroup of VRC were recorded. Results were as follows: 1. the hypoxic respiratory response was significantly attenuated after microinjection of genistein and/or CNQX, and no additive effect (i.e., further attenuation of hypoxic respiratory response) was observed when genistein and CNQX were microinjected one after another at the same injection site. Microinjection of daidzein had no effect on hypoxic respiratory response. 2. Fluorescent immunostaining showed that hypoxia significantly increased the number of phosphotyrosine immunopositive neurons in areas surrounding NA and most of these neurons were also immunopositive to glutamate AMPA receptor subunit GluR1. These results suggested that PTK played an important role in regulating the hypoxic respiratory response, possibly through the tyrosine phosphorylation modification of glutamate AMPA receptors on the respiratory neurons of ventral respiratory neuron column.